Application of a virtual reality-based cognitive-behavioural therapy of social phobia in the treatment of inpatients diagnosed with schizophrenia and social anxiety – a feasibility study - Stefaniak, Izabela; Aleksandrowicz, Adrianna (Frontiers in Psychiatry, 2024)
The co-occurrence of social anxiety symptoms and schizophrenia is a significant clinical problem. So far, social anxiety symptoms have been treated as an integral symptom of schizophrenia, receiving little attention as a target of direct therapeutic interventions. However, some evidence indicates that a high level of social anxiety in this group of patients may be a barrier to the recovery process. This feasibility study evaluated the use of a standard protocol for cognitive-behavioural therapy in the treatment of social phobia, in which social exposure was implemented with the usage of virtual reality (CBT + VRET). The study was conducted in a group of inpatients in a clinical psychiatric unit. Twenty inpatients diagnosed with schizophrenia and comorbid social anxiety symptoms were examined. Eleven patients were assigned to 10 weekly individual CBT+VRET interventions and nine to the control condition. Baseline and post-treatment assessments of social anxiety, psychotic symptoms, stigma, self-esteem, and depressive symptoms were measured before and after intervention. There was a decrease in social anxiety in the CBT+VRET group, while no such decrease was noted in the control group. This study provides preliminary evidence that CBT+VRET is acceptable, safe, and initial data that bears on the question of effectiveness for treating social anxiety disorder in people with schizophrenia. Future research should investigate the efficacy of CBT+VRET for the treatment of social anxiety symptoms and co-morbid schizophrenia in a larger randomised controlled trial.